2021
DOI: 10.3389/fendo.2021.722655
|View full text |Cite
|
Sign up to set email alerts
|

A Premature Rise of Luteinizing Hormone Is Associated With a Reduced Cumulative Live Birth Rate in Patients ≥37 Years Old Undergoing GnRH Antagonist In Vitro Fertilization Cycles

Abstract: This is a retrospective cohort study included 1021 patients underwent a flexible GnRH antagonist IVF protocol from January 2017 to December 2017 to explore the effect of a premature rise in luteinizing hormone (LH) level on the cumulative live birth rate. All patients included received the first ovarian stimulation and finished a follow-up for 3 years. A premature rise in LH was defined as an LH level >10 IU/L or >50% rise from baseline during ovarian stimulation. The cumulative live birth rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The result demonstrated that the P level on the trigger day was not an independent predictive factor of CLBR. The confounders included in the multivariate logistic model have been consistently reported to be associated with CLBR in previous studies [20][21][22]. The results of the present study are supported by another retrospective analysis of fresh oocyte donation cycles, which showed that excluding the detrimental effect of LFPE on endometrial receptivity, LFPE does not influence CLBR [4].…”
Section: Discussionsupporting
confidence: 86%
“…The result demonstrated that the P level on the trigger day was not an independent predictive factor of CLBR. The confounders included in the multivariate logistic model have been consistently reported to be associated with CLBR in previous studies [20][21][22]. The results of the present study are supported by another retrospective analysis of fresh oocyte donation cycles, which showed that excluding the detrimental effect of LFPE on endometrial receptivity, LFPE does not influence CLBR [4].…”
Section: Discussionsupporting
confidence: 86%
“…According to the analysis strati ed by ovarian response, a transient LH rise was not associated with a decline in pregnancy outcomes. Gao et al reported that the premature LH rise was associated with decreased rates of cumulative live birth rate in patients of advanced age (≥ 37 years) [11]. The inconsistent nding may be due to that they did not exclude the accompanying elevated serum progesterone level.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has reported the effect of a premature LH surge on the cumulative live birth rate (CLBR). The result indicated that the premature LH rise was associated with decreased rates of cumulative live birth rate in patients of advanced age (≥ 37 years) [11]. The limitation of the above study was that it did not exclude the accompanying elevated serum progesterone level.…”
Section: Introductionmentioning
confidence: 88%
“…In terms of premature LH surge rate, the two strategies showed a similar result (23.1% vs 25.2%, P=0.730), but the women in our study seem more likely to have premature LH surge during COS compared with previous studies ( 15 17 ). Numerous studies have reported low serum LH level ( 18 , 19 ), as well as high serum LH level during COS ( 9 , 19 ), would impair pregnancy and live birth outcomes. When it comes to the choice of GnRH-ant initiation strategy, according to previous studies, the inhibition effect of GnRH-ant on LH level did not differ between fixed or flexible GnRH-ant protocols, which are in accordance with our results ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women at AMA are a population with expected poor IVF-ET outcomes, and none of the current treatments or strategies showed truly uplifting results ( 6 , 7 ). According to previous studies, in addition to ovarian aging, AMA women also have the characteristics of a “relative LH deficiency” and are more prone to a “premature LH surge”, hence the dissatisfying outcomes ( 8 , 9 ). In light of these findings, the question arises: when is the optimal time to initiate GnRH-ant in AMA women in order to stabilize serum LH levels within a reasonable range and to optimize IVF-ET outcomes?…”
Section: Introductionmentioning
confidence: 99%